2020
DOI: 10.1073/pnas.1922719117
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni BumSR directs a response to butyrate via sensor phosphatase activity to impact transcription and colonization

Abstract: Campylobacter jejunimonitors intestinal metabolites produced by the host and microbiota to initiate intestinal colonization of avian and animal hosts for commensalism and infection of humans for diarrheal disease. We previously discovered thatC. jejunihas the capacity to spatially discern different intestinal regions by sensing lactate and the short-chain fatty acids acetate and butyrate and then alter transcription of colonization factors appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…Conversely, it has also been reported that Short Chain Fatty Acids (SCFAs), and especially butyrate can trigger the expression of C . jejuni genes that are important for host colonization, whereas lactate which is present in higher concentrations in the upper part of the digestive tract has an inhibitory effect on this expression [ 22 , 23 ]. In our study, F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it has also been reported that Short Chain Fatty Acids (SCFAs), and especially butyrate can trigger the expression of C . jejuni genes that are important for host colonization, whereas lactate which is present in higher concentrations in the upper part of the digestive tract has an inhibitory effect on this expression [ 22 , 23 ]. In our study, F .…”
Section: Discussionmentioning
confidence: 99%
“…Specific butyrate-sensing mechanisms have been recently described, altering transcription of target genes and being therefore proposed as a vital mechanism allowing C . jejuni to recognize and colonize specific intestinal niches [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the context of C. jejuni avian and human colonization, the abundance of butyrate and acetate in the lower GI tract provides the bacterium with a competitive advantage to thrive in this niche ( Burnham and Hendrixson, 2018 ). A prevailing belief is that C. jejuni has the ability to spatially differentiate between sections of the GI tract by sensing the presence of acetate and butyrate, and thereby modifying the transcription of its colonization factors ( Goodman et al., 2020 ). This enables C. jejuni to obtain sufficient nutrients and resources to allow for optimal survival and persistence in both avian and human intestinal tracts.…”
Section: Jejuni Fitness and Virulence Factors: Role In Stmentioning
confidence: 99%
“…This enables C. jejuni to obtain sufficient nutrients and resources to allow for optimal survival and persistence in both avian and human intestinal tracts. C. jejuni specifically senses butyrate via a noncanonical TCS termed BumSR ( Goodman et al., 2020 ). BumS functions as a phosphatase, via a noncanonical mechanism for signal transduction in place of a sensor kinase, to control the activity of the cognate BumR response regulator.…”
Section: Jejuni Fitness and Virulence Factors: Role In Stmentioning
confidence: 99%
“…These compounds commonly promote IL-10 production and suppress inflammation; however, they may also contribute toward effector T cell differentiation, depending on the overall local immunological context (Zhang et al, 2019). On the other hand, microbial metabolites in the intestine may stimulate virulence programs of invading bacteria, with several two-component signal transduction systems in T6SS-positive pathogens having been shown to respond to SCFAs and other metabolites produced by the microbiome (Lawhon et al, 2002;Gonzalez-Chavez et al, 2010;Kohli et al, 2018;Goodman et al, 2020). It is likely that T6SS-mediated turbulent population dynamics occurring during the microbiome development results in variation in the levels of these metabolites.…”
Section: Promotion Of Immune Homeostasis By the Microbiota: A Potentimentioning
confidence: 99%